Neuropeptidergic systems in psychiatric disorders - Hodzic, Sadat; Riedemann, Therese (Frontiers in Endocrinology, 2026)
Neuropeptides represent a heterogeneous class of signalling molecules whose release has initially been described in the hypothalamus. Their release often follows a circadian rhythm and basal release may be enhanced by internal and external stressors. Research on the cellular actions of neuropeptides began in the hypothalamus but progressed to the entire brain following observations of neuropeptide and neuropeptide receptor expression throughout the brain. Recent research suggests that the prefrontal cortex (PFC) exhibits particularly high levels of neuropeptides and neuropeptide receptors suggesting that they may modulate cognitive processes necessary for executive function. However, most data on the cellular actions of neuropeptides are derived from non-cortical cells and their relevance to PFC-dependent behaviour is currently not understood. This review aims to bridge the gap between cellular and network actions of neuropeptides and their relevance to behaviour and mood disorders. Therefore, this review summarises the function of the PFC and highlights the effects of selected neuropeptides on cortical processing and PFC-dependent behavioural output. Where available, we compare the actions of neuropeptides in the rodent brain to the human brain and review potential therapeutic benefits of neuropeptides in PFC-dependent neuropsychiatric disorders.